Phylogenetic signal and evolutionary correlates of urban tolerance in a widespread neotropical lizard clade. (28th March 2020) - Winchell, Kristin M.; Schliep, Klaus P.; Mahler, D. Luke; Revell, Liam J.
Abstract: Urbanization is intensifying worldwide, and while some species tolerate and even exploit urban environments, many others are excluded entirely from this new habitat. Understanding the factors that underlie tolerance of urbanization is thus of rapidly growing importance. Here, we examine urban tolerance across a diverse group of lizards: Caribbean members of the neotropical genus  Anolis . Our analyses reveal that urban tolerance has strong phylogenetic signal, suggesting that closely related species tend to respond similarly to urban environments. We propose that this characteristic of urban tolerance in anoles may be used to forecast the possible responses of species to increasing urbanization. In addition, we identified several key ecological and morphological traits that tend to be associated with tolerance in Anolis . Specifically, species experiencing hot and dry conditions in their natural environment and those that maintain higher body temperatures tend to have greater tolerance of urban habitats. We also found that tolerance of urbanization is positively associated with toepad lamella number and negatively associated with ventral scale density and relative hindlimb length. The identification of factors that predispose a species to be more or less urban tolerant can provide a starting point for conservation and sustainable development in our increasingly urbanized world.